International and ethnic variability of falls in older men. Issue 2 (March 2014) - Karlsson, Magnus K; Ribom, Eva L; Nilsson, J-Å; Karlsson, Caroline; Cöster, Maria; Vonschewelov, Thord; Mallmin, Hans; Ljunggren, Östen; Ohlsson, Claes; Mellström, Dan; Lorentzon, Mattias; Leung, PC; et al.
Aims : Fallers and especially recurrent fallers are at high risk for injuries. The aim of this study was to evaluate fall epidemiology in older men with special attention to the influence of age, ethnicity and country of residence. Methods : 10, 998 men aged 65 years or above recruited in Hong Kong, the United States (US) and Sweden were evaluated in a cross-sectional retrospective study design. Self-reported falls and fractures for the preceding 12 months were registered through questionnaires. Group comparisons were done by chi-square test or logistic regression. Results : The proportion of fallers among the total population was 16.5% in ages 65–69, 24.8% in ages 80–84 and 43.2% in ages above 90 ( P <0.001). The corresponding proportions of recurrent fallers in the same age groups were 6.3%, 10.1% and 18.2%, respectively ( P <0.001), and fallers with fractures 1.0%, 2.3% and 9.1%, respectively ( P <0.001). The proportion of fallers was highest in the US, intermediate in Sweden and lowest in Hong Kong (in most age groups P <0.05). The proportion of fallers among white men in the US was higher than in white men in Sweden (all comparable age groups P <0.01) but there were no differences in the proportion of fallers in US men with different ethnicity. Conclusions : The proportion of fallers in older men is different in different countries, and data in this study corroborate with the view that society of residence influences fall prevalence more than ethnicity.